MANAJEMEN PROYEK KONSTRUKSI PEMBANGUNAN REVETMENT DI TELUK MANADO (KOMPLEK PASAR BERSEHATI) - Toufan Matindas; Rifana Kawet; Yessy Pandeiroth, (Sustainable Construction (SUSCON), 2024)
This research aims to 1) find out the estimated time by implementing EVM (Earned Value Management) during the implementation time so that it is in accordance with the initial plan for the revetment construction project in Manado Bay, and 2) Find out the additional costs of the project when experiencing delays and acceleration. This research is located at the construction of a revetment in the Bersehati market complex, Manado city. Data analysis uses the Earned Value Concept method. The research results show that in the 19th week, the ETC calculation reached IDR 50,896,353,625.36 from the initial budget of IDR 11,120,996,728, with a deviation in the increase in budget value of -IDR 5,562,722,563.35. The estimated time for project completion in the 19th week was 86.8 days, indicating that completion was delayed by around 167 days from the original plan, which should have been only 20 days.